Implementation Of The Basic Learning Problem Method Case Study In Islamic Religious Education At Wijaya Kusuma Banjar Margo Junior High School, Tulang Bawang Regency - Anam, Khoirul; Pangeran, Giman Bagus; Azizeh, Nur (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Islamic Religious Education (IRE) at Wijaya Kusuma Banjar Margo Junior High School in Tulang Bawang Regency and analyze its impact on student activity and critical thinking skills. The background of this study is based on low learning interest, student participation, and PAI learning outcomes that have not reached the minimum completion criteria due to the dominant use of lecture methods in the learning process. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and documentation, with research subjects including the principal, PAI teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the application of the Problem-Based Learning model in PAI learning is able to increase student engagement, encourage critical thinking skills, and help students understand the material through problem solving related to everyday life. Students become more courageous in expressing their opinions, working together in groups, and taking responsibility for the learning process. However, the implementation of PBL has not been optimal due to limited learning time, differences in student characteristics, and student readiness to participate in problem-based learning. Thus, the Problem Based Learning model can be an effective alternative learning strategy in improving the quality of Islamic Religious Education learning if it is supported by careful planning and good time management and adequate infrastructure support.